Training in computational chemistry and its applications through a research project developed in the Chilean Patagonia Formación en química computacional y sus aplicaciones a través de un proyecto de investigación desarrollado en la Patagonia chilena - Oyarzún Aravena, Andrea María; Moya-Barría, Iván I.; Navarro Pérez, Daniela Josefina (My University, 2022)
This study assesses the pedagogical benefits obtained by students, teachers, and a sponsor through the development of a computational chemistry research project on interactions between carbon materials and gases. Achievements, challenges, and opportunities are identified, emphasizing the mastery of transferable and technical skills throughout the four-year-long project. Engineering thesis students formed the teamwork. We highlight the implementation of the servers and software which are necessary to apply computational chemistry as a methodological tool. The subject of air pollution is also examined by performing a multidisciplinary analysis that determines potential areas for future applications and the impact of the computational analyses performed. It is concluded that there is development of training abilities in complex scientific-technological areas for both undergraduate and graduate students in a geographically isolated context that may limit performance.
Keywords: análisis pedagógico; computational chemistry; multidisciplinario; multidisciplinary; pedagogical analysis; química computacional; tesis pregrado; undergraduate thesis